Are there sex differences in potentially inappropriate prescribing in adults with multimorbidity?. Issue 8 (6th May 2021) - Ukhanova, Maria; Markwardt, Sheila; Furuno, Jon P.; Davis, Laura; Noble, Brie N.; Quiñones, Ana R.
Abstract: Background/objectives: Limited knowledge exists regarding sex differences in prescribing potentially inappropriate medications (PIMs) for various multimorbidity patterns. This study sought to determine sex differences in PIM prescribing in older adults with cardiovascular‐metabolic patterns. Design: Retrospective cohort study. Setting: Health and Retirement Study (HRS) 2004–2014 interview data, linked to HRS‐Medicare claims data annualized for 2005–2014. Study sample: Six thousand three‐hundred and forty‐one HRS participants aged 65 and older with two and more chronic conditions. Measurements: PIM events were calculated using 2015 American Geriatrics Society Beers Criteria. Multimorbidity patterns included: "cardiovascular‐metabolic only, " "cardiovascular‐metabolic plus other physical conditions, " "cardiovascular‐metabolic plus mental conditions, " and "no cardiovascular‐metabolic disease" patterns. Logistic regression models were used to determine the association between PIM and sex, including interaction between sex and multimorbidity categories in the model, for PIM overall and for each PIM drug class. Results: Women were prescribed PIMs more often than men (39.4% vs 32.8%). Overall, women had increased odds of PIM (Adj. odds ratio [OR] = 1.30, 95% confidence interval [CI]: 1.16–1.46). Women had higher odds of PIM than men with cardiovascular‐metabolic plus physical patterns (Adj. OR = 1.25, 95% CI: 1.07–1.45) and cardiovascular‐metabolic plus mental patterns (Adj. OR = 1.25, 95% CI: 1.06–1.48), and there were no sex differences in adults with a cardiovascular‐metabolic only patterns (Adj. OR = 1.13, 95% CI: 0.79–1.62). Women had greater odds of being prescribed the following PIMs: anticholinergics, antidepressants, antispasmodics, benzodiazepines, skeletal muscle relaxants, and had lower odds of being prescribed pain drugs and sulfonylureas compared with men. Conclusion: This study evaluated sex differences in PIM prescribing among adults with complex cardiovascular‐metabolic multimorbidity patterns. The effect of sex varied across multimorbidity patterns and by different PIM drug classes. This study identified important opportunities for future interventions to improve medication prescribing among older adults at risk for PIM.